Chapter 10 Norway - Ellefsen, Rune (Taylor & Francis, 2023)
The last decade has witnessed growing concern about violent extremism as many European countries have introduced policies to prevent and counter violent extremism (P/CVE). Norway is no exception, launching three such action plans. Having also suffered from an extensive history of right-wing extremism, Norway was once the scene of the relatively successful pioneering of the European EXIT programme. However, extremist groups today are more socially complex and in rethinking how society can strengthen P/CVE approaches through social networks, 'resilience' has emerged as a key element of what might make people resistant to violence and extremism. This chapter provides an overview of developments in violent extremism in Norway over the last decades, and the social and political responses to it. We examine how resilience manifests in policy and how it relates to P/CVE practice, as well as discuss the implications of Norwegian P/CVE approaches. We distinguish between security-oriented and pro-social approaches to resilience and explore how this differentiation may be used to highlight an antagonism between securitisation and social transformation. In our conclusion, we suggest deemphasising securitised P/CVE approaches in favour of developing pro-social forms of resilience to violent extremism in Norway.